Computer Anxiety, Computer Self Efficacy, Pemahaman Akuntansi dan Minat Mahasiswa Menggunakan Software Akuntansi - Kusmaeni, Emi; Nugraheni, Ratna; Syahrenny, Nenny; Sulistyowati, Endah (E-Jurnal Akuntansi, 2022)
The purpose of this research is to assess the factors that influence learning interest in using software and to find out the shortcomings that occur in the learning process so that it can improve the learning process strategy. The research population is the 2018-2019 class of students with a total of 338 students being the research sample. Statistics used multiple linear regression analysis. The results showed that computer anxiety and computer self-efficacy had a significant effect on students' interest in using accounting software. While the understanding of accounting has no effect on student interest. So it can be concluded that the variables of computer anxiety, computer self-efficacy, and understanding of accounting have a significant effect on students' interest in using accounting software. Keywords: Computer Anxiety; Computer Self Efficacy; Students’ Interest; Accounting Software